Meteorological Influence of Mineral Dust Distribution Over South-Western Africa Deserts Using Reanalysis and Satellite Data - Shikwambana, Lerato; Kganyago, Mahlatse (Frontiers in Environmental Science, 2022)
Mineral dust is a major component of the atmospheric aerosol load with the strongest source regions located in the Saharan desert. Long-range transport of desert dust from the Sahara across the northern Atlantic has been recorded many times by satellite imagery and ground-based measurements. In south-western Africa, the Namib and the Kalahari deserts are the likely sources for the transport and distribution of mineral dust. Therefore, in this study, we report on the seasonal transport and distribution of mineral dust in the south-western African region using satellite and reanalysis datasets. The results show that the Namib desert is the main source of dust in the region, with seasonal variations. The greatest distribution of dust is observed in the June-July-August (JJA) season and the southwesterly winds are accountable for the transport of dust into the interior. The highest dust aerosols were observed at altitudes of 7.05 km, 7.29 km and 10.28 km, respectively. Favourable meteorological parameters played a vital role in the production and distribution of dust aerosols. This study is important because it could be used as a basis to investigate desertification, primarily from a climate change point of view, in Southwest Africa.